2019
DOI: 10.1074/mcp.ra118.001125
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of the 2016 WHO Neisseria gonorrhoeae Reference Strains Surveys Vaccine Candidates and Antimicrobial Resistance Determinants

Abstract: We present the first large-scale quantitative MS-based profiling of cell envelopes and cytoplasmic proteins derived from a diverse panel of WHO gonococcal reference strains possessing all existing AMR profiles and intended for quality assurance in laboratory investigations. We describe nine novel gonorrhea vaccine candidates and six potential global proteomic AMR markers. A reference proteomics databank for gonococcal vaccine and AMR research endeavors is provided, which enables microbiological, clinical, or e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 150 publications
(146 reference statements)
1
20
0
Order By: Relevance
“…In our study, we observed that the expression of MtrR in the ESC-resistant isolates were downregulated, suggesting decreased repression of the MtrCDE efflux pump, thereby increasing cellular expulsion of antimicrobials. This is consistent with findings that decreased expression of MtrR is associated with increased CRO MICs (El-Rami et al, 2019). Expression of a predicted membrane protein (A0A1D3E8W0) was upregulated in the three ESC-resistant isolates.…”
Section: Proteins Involved In Permeability Of Cell Membranessupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, we observed that the expression of MtrR in the ESC-resistant isolates were downregulated, suggesting decreased repression of the MtrCDE efflux pump, thereby increasing cellular expulsion of antimicrobials. This is consistent with findings that decreased expression of MtrR is associated with increased CRO MICs (El-Rami et al, 2019). Expression of a predicted membrane protein (A0A1D3E8W0) was upregulated in the three ESC-resistant isolates.…”
Section: Proteins Involved In Permeability Of Cell Membranessupporting
confidence: 91%
“…Expression of a predicted membrane protein (A0A1D3E8W0) was upregulated in the three ESC-resistant isolates. However, the expression of this protein was downregulated in the WHO-L N. gonorrhoeae strain that was ESC-resistant (El-Rami et al, 2019). In El-Rami's study, proteomic analysis was performed on proteins of subcellular fractionation, whereas in the present study, proteomic analysis was conducted on proteins from the whole cell extracts.…”
Section: Proteins Involved In Permeability Of Cell Membranesmentioning
confidence: 83%
See 3 more Smart Citations